Operative experience on descending aorta with Takayasu Arteritis: a review - Fu, Yining; Chen, Yuexin (Frontiers in Cardiovascular Medicine, 2023)
Patients with Takayasu arteritis (TA) and descending aorta involvement often experience insidious onset and slow progression, leading to irreversible vascular lesions despite medication therapy. Surgical management plays a crucial role in resolving hemodynamic disturbances and has shown promise in improving the outcomes of this patient population, owing to significant advancements in surgical expertise. However, studies focusing on this rare disease are lacking. This review summarizes the characteristics of patients with stenosis in descending aorta, emphasizing surgical approaches, perioperative management, and disease outcomes. The operative approach depends on lesion location and extent. Existing studies have confirmed that the choice of surgical modality significantly influences postoperative complications and long-term prognosis in patients, highlighting the effectiveness of bypass surgery as a favorable option in clinical practice with a satisfactory long-term patency rate. To mitigate postoperative complications, it is advisable to conduct regular imaging follow-ups to prevent the deterioration of the condition. Notably, the occurrence of restenosis and pseudoaneurysm formation deserves particular attention due to their impact on patient survival. The use of perioperative medication remains a topic of debate, as previous studies have presented divergent perspectives. The primary objective of this review is to provide a comprehensive perspective on surgical treatment and offer customized surgical approaches for patients in this population.